Rare primary bladder mucosa-associated lymphoid tissue lymphoma: A case report and review of literature - Tu, Xi; Zhuang, Xiyao; Li, Fen; Huang, Chaoyou; Qian, Youliang (Frontiers in Oncology, 2023)
Primary bladder mucosa-associated lymphoid tissue (MALT) lymphoma is an extremely rare bladder tumor. Only scarce reports have been reported. We hereby report a case of an 81-year-old female patient with bladder tumor presenting with frequent urination and dysuria, whose pelvic magnetic resonance imaging (MRI) considered bladder cancer. She underwent transurethral resection of the bladder tumor (TURBT), and histopathology confirmed the mass to be bladder MALT lymphoma. The patient refused further treatment, and no disease recurrence one year after surgery. The current data are insufficient to draw conclusions about the long-term efficacy of treatment for this tumor, regular follow-up is necessary. To further understand the clinical features, pathology, treatment and prognosis of this tumor, we have searched the literature from 1990 to the present, analyzing a total of 64 cases of primary MALT lymphoma.